Menuju Kewirausahaan Sosial di Desa melalui Badan Usaha Milik Desa: Towards Social Entrepreneurship in the Village through Village-Owned Enterprises - Muryanti Muryanti (Society, 2020)
Social entrepreneurship is an important concept for realizing the welfare of rural communities. This concept refers to the dedication of individuals, who have the character of a leader, who collaborates actively with their communities, to realize collective welfare. This research aims to analyze the role of Village-Owned Enterprises (BUMDes) in improving the welfare of rural communities through social entrepreneurship. This research was qualitative. The data collection technique used in this research was the observation. The results of observations are then analyzed, combined, and enriched with secondary data. The results showed that BUMDes is an institution in rural areas, which has an important role in encouraging and supporting the principles of social entrepreneurship in rural communities. However, the various BUMDes activities and innovations have not yet provided significant changes for the village such as job opportunities for rural youth and various economic activities in rural areas to improve the local economy. Strengthening the social system in the village is needed to realize social entrepreneurship comprehensively through the active collaboration of village leaders and the community. Village fund management by BUMDes needs to be continued and evaluated in its implementation.